Modulation of B cell receptor activation by antibody competition - He, Yuanyuan; Guo, Zijian; Vahey, Michael D. (Cell reports (Cambridge), 2025)
During repeated virus exposure, pre-existing antibodies can mask viral epitopes by competing with B cell receptors for antigen. Although epitope masking has the potential to steer B cell responses away from conserved epitopes and toward those that are antigenically novel, the factors that influence this process remain unclear. Using engineered, influenza-reactive B cells, we investigate how antibodies affect the accessibility of epitopes on the viral surface. We find that antibodies against either hemagglutinin or neuraminidase frequently inhibit B cell activation, including, in some instances, B cells targeting the other viral surface protein. Within hemagglutinin, the potency of masking depends on the proximity and relative location of the targeted epitopes as well as antibody affinity, kinetics, and valency. Although most antibodies are inhibitory, we identify one that can enhance accessibility of sites within the hemagglutinin trimer interface. Together, these findings establish rules for epitope masking that could help advance immunogen design. [Display omitted] •B cells targeting HA epitopes are sensitive to direct antibody competition•Membrane-proximal epitopes on HA are subject to both direct and indirect masking•HA-stalk antibodies can inhibit activation of B cells targeting NA•Slow antibody dissociation kinetics enhance the potency of epitope masking Antibodies from prior exposure to influenza viruses affect immune responses during subsequent encounters. He et al. establish an in vitro system that mimics B cell extraction of viral antigens and use it to study principles of epitope masking, demonstrating a dynamic competition between soluble antibodies and B cell receptors.